Eine Untersuchung über die Wasserführung des Bodens in Abhängigkeit vom Witterungsablauf und von der Vegetationsbedeckung - Borchert, Günter (ERDKUNDE, 1956)
During the two growing seasons of 1951 and 1952 the author carried out an investigation into the changes of soil humidity. Measurements were made at two points in the Elbmarsch near Uetersen; point one was situated in an orchard and point two on a spot devoid of vegetation. After explaining the methods employed for measuring and representing the results, the paper deals with the interpretation of the diagrams of soil humidity change at these two points. The area devoid of vegetation showed a greater tonal humidity in the investigated soil column of one metre in depth than the area with a vegetation cover. On the other hand, the minimum and maximum values of soil humidity, 12.5 and 51 per cent respectively, were found in the latter, as can be seen in the diagram. The soil moisture stored up during the winter and reaching to between 40 and 25 cm beneath the surface, is only available for the budding trees in spring; later on the zone from which moisture is drawn increases down to a depth of 80 cm, and it may be assumed that in this zone so much warmer is extracted that eventually the soil becomes physiologically dry. During the summer months the zone near the surface is of great importance for providing the fruit trees with the necessary water. By loosening the soil around the tree, and mulching, as well as through a biological process which is induced by the shade of the trees, the soil structure becomes changed in such a way that the surface layer of soil is able to absorb like a sponge the water of the heavy summer rains, whereas in the area without vegetation the rain water runs off on the surface. A stand of trees draws large amounts of water from the ground; the loose soil of the surface zone beneath the trees, well sheltered from the action of wind and sunrays is, however, able to store water. As can be seen from the description of the soil and from the soil humidity values of the diagram it would be wrong to classify the soil of the area where orchards are found in the Marsch as wet. It is the method of cultivation which has created an artificial forest soil. It must be left to further investigations to find out whether similar measures for regulating the soil humidity regime can also be applied in other climatic zones.